2019
DOI: 10.1108/heswbl-03-2018-0025
|View full text |Cite
|
Sign up to set email alerts
|

Internship in a business school: expectation versus experience

Abstract: Purpose The purpose of this paper is to evaluate the value of internship as a function of the disparity between the initial expectation from the internship and its actual experience. The perceived internship experience has been evaluated through the expectation confirmation theory (ECT). Design/methodology/approach A sample of 106 students pursuing Master of Business Administration in a business school in India were administered a questionnaire to assess their expectations and experience before and after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 71 publications
2
28
0
Order By: Relevance
“…Furthermore, mentors can support goal setting and achievement. This would be in line with work that has shown that the “perceived value of the supervisor-intern exchange has a significant relationship with perceived internship value” (Neelam et al , 2019, pp. 92).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Furthermore, mentors can support goal setting and achievement. This would be in line with work that has shown that the “perceived value of the supervisor-intern exchange has a significant relationship with perceived internship value” (Neelam et al , 2019, pp. 92).…”
Section: Discussionsupporting
confidence: 88%
“…Prior research has shown that when interns have a clear understanding of what they need to achieve, they are more likely to be both effective and satisfied (Kapareliotis et al , 2019). The lower the discrepancy between internship expectations and the actual experience, the higher interns' satisfaction (Neelam et al , 2019). This suggests that communication before and during the internship (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the application was tested in the graduate-level educational environment, so findings are not generalizable to other student levels or fields of study. However, findings are in-line with various other studies that reported similar benefits of applied learning techniques (Brown et al, 2018;Silva et al, 2018;Bhattacharya and Neelam, 2018). Larger samples using a variety of applications should continue to be explored.…”
Section: Limitationssupporting
confidence: 89%
“…Hence, it is important that future managers first study different aspects of a decision, then consider them in totality and not in isolation. Several opportunities do exist for advanced learning in applied settings, such as internships, residencies and practical learning courses such as capstone projects with industry clients (Brown et al, 2018;Silva et al, 2018;Bhattacharya and Neelam, 2018). However, this option of applied learning is also available for basic and intermediate courses to meet the changing demands of the student.…”
Section: Introductionmentioning
confidence: 99%